Comparison of performance statistics of CT scan and ultrasonography in complicated appendicitis: experience in a tertiary care centre - Majhi, Harekrishna; Panigrahi, Pramit Ballav; Mohapatra, Abinasha (International Journal of Research in Medical Sciences, 2020)
Background: This study is conducted from November 2018 to November 2019 in this institute, where comparison of performance statistics is done between CT scan and Ultrasonography in patients with complicated appendicitis scheduled for conservative management, elective or emergency surgery. Aim of the study was to evaluate and compare the performance statistics of CT scan and Ultrasonography in complicated appendicitis. Methods: The CT scan or USG findings of 87 patients were reviewed. The patients were divided into two groups i.e. CT scan group (group-1/18 patients), USG group (group-2/69 patients). Satistical analysis Student”s t-test, Fischer”s test, p-value, k-value. Results: Clinical signs, CT findings, USG findings, complications at surgery and histological examinations were noted. 2, 3, 13, patients presenting with CT features and 5, 13, 51 patients presenting with USG features of appendicular perforation, peri-appendicular abscess, inflammatory appendicular mass respectively. No clinical signs showed a significant association with the presence of appendicular perforation, peri-appendicular abscess, inflammatory appendicular mass or the complication encountered at surgery. Conclusions: In this study, by comparing CT scan group and USG group in complicated acute appendicitis, CT scan can change the plan of management in doubtful cases, decrease length of hospital stay and expenses, reduce the complication rate and negative laparotomy rate, and reduce the episodes of conversion to open surgery.